Analisis Perbedaan Diktum Biaya Penyelesaian Perkara Sengketa Ekonomi Syariah - Burhanudian Manilet; Fairuz Sabiq; Indah Mustika (Jurnal Hukum Lex Generalis, 2025)
This study analyzes decisions on sharia economic disputes, particularly simple lawsuit decisions at the Sukoharjo Class IB Religious Court. The focus of this study is the difference in the granting of case settlement costs in the considerations and dictum of the decision imposed on defendants who are proven to be in default. The purpose of this study is to understand the judges' reasoning, thereby identifying why there are differences in the allocation of case resolution costs for the defendant in summary judgments within the same legal jurisdiction. The research method used is a normative legal study, targeting written regulations or legal materials in the form of court decisions, specifically Decision No. 3/Pdt.G.S/2024/PA.Skh. The data sources include court decisions, laws, PERMA, and ministerial decisions, which will be presented narratively with deductive analysis in accordance with the theoretical framework used. The conclusion obtained from this study is that the judge's consideration in determining the burden of the cost of resolving a simple lawsuit in the sharia economy does not consider the radius of domicile of the parties, so that the burden of the case settlement fee becomes different in the amount of burden, even though it is in the same jurisdiction. And what is suggested from this study is the importance of new regulations as a guideline in determining the burden of collection/settlement costs